1996
DOI: 10.1007/bf01093214
|View full text |Cite
|
Sign up to set email alerts
|

Physical and nutritional qualities of extruded weaning foods containing sorghum, pearl millet, or finger millet blended with mung beans and nonfat dried milk

Abstract: Sorghum, pearl millet, and finger millet flours (60% of each) were blended with toasted mung bean flour (30%) and nonfat dry milk (10%) and extruded (Brabender single screw) to make precooked, ready-to-eat, weaning foods. The extruded foods had high cold paste viscosity, but their cooked paste viscosity was lower than that of the respective blends. Chemical scores of the extruded foods were 78 for sorghum, 80 for pearl millet, and 96 for finger millet. Protein digestibility corrected amino acid scores (PD-CAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 11 publications
4
16
0
Order By: Relevance
“…The decrease in SDF and increase in IDF fractions indicates the increased fibre availability for faecal bulking and water binding in the colon resulting in more frequent and softer bowel motions, reduced risk of constipation and increased volume of waste material (Onyango et al 2004). In contrast, extrusion processing increases approximately 10% soluble dietary fiber than the unprocessed cereal based weaning foods (Malleshi et al 1996).…”
Section: Composition Of the Millet Df And Changes In Contents During mentioning
confidence: 99%
“…The decrease in SDF and increase in IDF fractions indicates the increased fibre availability for faecal bulking and water binding in the colon resulting in more frequent and softer bowel motions, reduced risk of constipation and increased volume of waste material (Onyango et al 2004). In contrast, extrusion processing increases approximately 10% soluble dietary fiber than the unprocessed cereal based weaning foods (Malleshi et al 1996).…”
Section: Composition Of the Millet Df And Changes In Contents During mentioning
confidence: 99%
“…The acid‐treated pearl millet yields products of better acceptability as compared to that from just decorticated pearl millet. Sorghum and pearl millet, blended with soy or protein‐rich ingredients, such as legumes or groundnut (peanut) cake, on extrusion give nutritionally balanced supplementary foods (Malleshi and others 1996). Sumathi and others (2007) showed that extruded pearl millet products prepared from a blend of 30% grain legume flour or 15% defatted soybean had, respectively, 14.7% and 16.0% protein, and 2.0 and 2.1 protein efficiency ratio.…”
Section: Adaptation and Potential Uses Of Sorghum And Pearl Millet Inmentioning
confidence: 99%
“…Sorghum, pearl millet, and finger millet flours were blended with toasted mung bean flour and nonfat dry milk and extruded to make ready-to-eat weaning foods (Malleshi et al 1996). Pearl millet is a course cereal grain and has equivalent or even superior nutrient content to other cereals (Obilana and Manyasa 2002).…”
Section: Introductionmentioning
confidence: 99%